A multi‐omics framework reveals strawberry flavor genes and their regulatory elements. Issue 3 (20th August 2022) - Fan, Zhen; Tieman, Denise M.; Knapp, Steven J.; Zerbe, Philipp; Famula, Randi; Barbey, Christopher R.; Folta, Kevin M.; Amadeu, Rodrigo R.; Lee, Manbo; Oh, Youngjae; Lee, Seonghee; Whitaker, Vance M.
Summary: Flavor is essential to consumer preference of foods and is an increasing focus of plant breeding programs. In fruit crops, identifying genes underlying volatile organic compounds has great promise to accelerate flavor improvement, but polyploidy and heterozygosity in many species have slowed progress. Here we use octoploid cultivated strawberry to demonstrate how genomic heterozygosity, transcriptomic intricacy and fruit metabolomic diversity can be treated as strengths and leveraged to uncover fruit flavor genes and their regulatory elements. Multi‐omics datasets were generated including an expression quantitative trait loci map with 196 diverse breeding lines, haplotype‐phased genomes of a highly‐flavored breeding selection, a genome‐wide structural variant map using five haplotypes, and volatile genome‐wide association study (GWAS) with > 300 individuals. Overlaying regulatory elements, structural variants and GWAS‐linked allele‐specific expression of numerous genes to variation in volatile compounds important to flavor. In one example, the functional role of anthranilate synthase alpha subunit 1 in methyl anthranilate biosynthesis was supported via fruit transient gene expression assays. These results demonstrate a framework for flavor gene discovery in fruit crops and a pathway to molecular breeding of cultivars with complex and desirable flavor.